The Effect of Frugal Living on Purchase Decisions among Generation Z: The Mediating Role of Financial Well-Being - Yuvita, Heni; Permatasari, Imas (Jurnal Sains Sosio Humaniora, 2025)
This study examines the effect of frugal living on purchase decisions among Generation Z and investigates the mediating role of financial well-being in this relationship. As Generation Z faces increasing exposure to digital consumption trends and financial challenges, understanding the mechanisms that influence their purchasing behavior has become increasingly important. A quantitative research design was employed using a cross-sectional survey approach. Data were collected from 125 Generation Z respondents selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that frugal living has a significant positive effect on financial well-being, while financial well-being significantly influences purchase decisions. However, the direct effect of frugal living on purchase decisions was not significant. Further analysis revealed that financial well-being fully mediates the relationship between frugal living and purchase decisions. These results suggest that frugal living contributes to more responsible purchasing behavior only when it enhances individuals’ financial security, confidence, and financial control. The study extends the literature on consumer behavior by highlighting financial well-being as a key explanatory mechanism linking lifestyle choices and purchasing decisions. Practically, the findings emphasize the importance of financial literacy and financial well-being initiatives in promoting responsible consumption among Generation Z consumers.